FINANCIAL ANALYSIS MAINTENANCE OF LAYER CHICKEN INTENSIVELY WITH OPEN HOUSE BATTERY CAGE SYSTEM (Case Study at Arcana Poultry Farm, Candikusuma Village Melaya District, Jembrana Regency) - M. Y., Simbolon; M. Y., Simbolon; Mahardika, I G.; Sukanata, I W. (Jurnal Peternakan Tropika; Vol 10 No 1 (2022): Vol. 10 No. 1 Tahun 2022; January - april, 2022)
This study aims to determine the financial aspects (income, R/C ratio, production break-even point and egg price break-even point) laying hens that are kept in open house cages with a capacity of 1,500 layer. This study was conducted at Arcana Poultry, Candikusuma Village, Melaya District, Jembrana Regency – Bali. which was carried out for 3 weeks from January 1 to January 20, 2021. The variables observed were production performance and income analysis. Production performance consisted of average egg production, depletion and acceptance. while the income analysis consists of depreciation costs, fixed costs and variable costs, income, R/C Ratio , and BEP ( break even point ). The results showed that the eggs produced by lohmann brown chickens aged 26 weeks-28 weeks were 42 trays or 1.253 eggs/day, with hen day production of 83,5% /day and depletion of 0,06%, the net income of farmers was Rp. 131.118, -/day with R/C Ratio of 1,10, BEP unit of 746 eggs/day, BEP price of Rp. 1.018/egg and BEP sales of Rp. 832.536,-/day.   Key words: income, R/C Ratio, break-even point